Assessing long-term spatio-temporal variability in humidity and drought in Iran using Pedj Drought Index (PDI). (February 2021) - Lashkari, Azam; Irannezhad, Masoud; Zare, Hossein; Labzovskii, Lev
Abstract: Although drought is a normal feature of climate, there is confusion about its characteristics in both arid and semi-arid regions. This study investigated the effects of changes in precipitation and temperature on spatio-temporal drought and humidity variations throughout the diverse (principally arid- and semi-arid) climates of Iran during recent decades using the Pedj Drought Index (PDI). The standardized anomaly index (SAI) for annual precipitation (SAIPr ) and mean temperature (SAITm ) was calculated using their monthly records at sixteen meteorological stations scattered throughout Iran during 1951–2010. The results showed: (1) statistically significant (p < 0.05) drying trends in annual PDI values at most of the stations, primarily accompanied by substantial increases in annual SAITm ; (2) considerable positive and negative relationships of annual PDI with annual SAITm and SAIPr, respectively; (3) the 1970s/2000s as the predominant humid/dry decade; (4) More frequent drought than humidity events at ~81% of stations; (5) the longest drought was 13 years (1998–2010) seen at the Kermanshah station, with the semi-dry climate in the west of Iran; and (6) the 2010 drought spatially extended over all the stations studied throughout the country. In conclusion, the PDI acceptably succeeded to characterize annual droughts in Iran previously captured by other prominent recommended drought indices. Highlights: Pedj drought index (PDI) successfully characterized historical dryness in Iran. Temperature warming was the dominant driver for severe historical droughts in Iran. The 1970s/2000s was the predominant humid/dry decades in Iran. More frequent drought than humidity events throughout Iran in 1951–2010. Mega-droughts spatially extended in Iran were generally seen after 1997.